Creator : an interactive, team-based inter-organisational cost management exercise - Afonso, Paulo (2012)
IOCM practices can play a relevant role guiding effective NPD processes, reducing time-to-market and helping managers in the development of competitive products. The authors have developed an in-class exercise on IOCM. This exercise can be used to involve students or practitioners in a dynamic process where a NPD process is enhanced by the use of several cost management techniques. This exercise has been applied in the academic year of 2008/09 by two teams of students. The exercise and was designed considering previous work (Cook and Hazelwood, 2002; Castellano and Young, 2003; Everaert et al., 2008). Nevertheless, several changes, adaptations and improvements were made. This work offers a basis for further replications in a classroom setting and also can be used to demonstrate the features of inter-organisational cost management practices in NPD processes to an audience of practitioners.